Tensile and bonding behaviours of hybridized BFRP–steel bars as concrete reinforcement. (20th March 2019) - Ma, Guowei; Huang, Yimiao; Aslani, Farhad; Kim, Timothy
Highlights: A hybridized basalt fibre–reinforced polymer and steel (BFRP-steel) rebar is proposed in this study. The proposed method aims at providing a possible anticorrosive reinforcement for concrete components. The hybridized BFRP-steel bar enabled a more balanced tensile behaviour between steel and FRP reinforcements. The bond strength of the proposed hybridized bar was investigated based on four types of surface treatments. Abstract: Corrosion of steel increases the cost of maintenance and reduces the long-term performance of steel-reinforced concrete structures. Fibre reinforced polymer (FRP) bars have been developed as promising alternatives. However, the application of FRP bars is limited by high initial cost, low elastic modulus, and brittleness. Therefore, a hybridized basalt FRP and steel (BFRP-steel) rebar is proposed to provide another possible anticorrosive reinforcement for concrete. The proposed rebar protects the steel core with BFRP wrap, and the low cost of steel improves the feasibility of using fibre reinforcement by significantly reducing the total material cost. Four BFRP-steel and seven glass FRP bars were experimentally tested to investigate their tensile strength. Results showed that the hybridized bars allowed a more balanced tensile behaviour, which not only improved the ultimate tensile strength by 47% compared with steel reinforcement, but also overcame the shortage of FRP bar's low elastic modulus by introducing a 169% improvement. Meanwhile, the bond strengths of the FRP bars was tested by pullout tests of four groups of surface treatments. Results indicated that the sand-coating treatment had the highest level of bonding capacity but had a brittle failure mode. A more ductile but less strong bonding behaviour could be achieved by combining the surface treatment of the sand-coating with spiral-wounding.